Validation of the new Sepsis-3 definitions: proposal for improvement in early risk identification. (February 2017) - Giamarellos-Bourboulis, E.J.; Tsaganos, T.; Tsangaris, I.; Lada, M.; Routsi, C.; Sinapidis, D.; Koupetori, M.; Bristianou, M.; Adamis, G.; Mandragos, K.; Dalekos, G.N.; Kritselis, I.; et al.
Abstract: Objectives: Sepsis-3 definitions generated controversies regarding their general applicability. The Sepsis-3 Task Force outlined the need for validation with emphasis on the quick Sequential Organ Failure Assessment (qSOFA) score. This was done in a prospective cohort from a different healthcare setting. Methods: Patients with infections and at least two signs of systemic inflammatory response syndrome (SIRS) were analysed. Sepsis was defined as total SOFA ≥2 outside the intensive care unit (ICU) or as an increase of ICU admission SOFA ≥2. The primary endpoints were the sensitivity of qSOFA outside the ICU and sepsis definition both outside and within the ICU to predict mortality. Results: In all, 3346 infections outside the ICU and 1058 infections in the ICU were analysed. Outside the ICU, respective mortality with ≥2 SIRS and qSOFA ≥2 was 25.3% and 41.2% (p <0.0001); the sensitivities of qSOFA and of sepsis definition to predict death were 60.8% and 87.2%, respectively. This was 95.9% for sepsis definition in the ICU. The sensitivity of qSOFA and of ≥3 SIRS criteria for organ dysfunction outside the ICU was 48.7% and 72.5%, respectively (p <0.0001). Misclassification outside the ICU with the 1991 and Sepsis-3 definitions into stages of lower severity was 21.4% and 3.7%, respectively (p <0.0001) and 14.9% and 3.7%, respectively, in the ICU (p <0.0001). Adding arterial pH ≤7.30 to qSOFA increased sensitivity for prediction of death to 67.5% (p 0.004). Conclusions: Our analysis positively validated the use of SOFA score to predict unfavourable outcome and to limit misclassification into lower severity. However, qSOFA score had inadequate sensitivity for early risk assessment.